Preparing for the interviewing process during Coronavirus disease-19 pandemic: Virtual interviewing experiences of applicants and interviewers, a systematic review - Chandratre, Sonal (PLoS One, 2020)
PURPOSE: Coronavirus disease-19 (COVID-19) has forced upon all academic institutions to conduct virtual interviewing (VI) instead of face-to-face interviewing (FTFI) this interviewing cycle. The purpose of this systematic review was to understand the process of VI, its effectiveness as an alternative to FTFI, and the experiences of applicants and institutions with VI. We also share best practice strategies for applicants and institutions in VI preparation. METHOD: PubMed/MEDLINE, Cochrane Library of Systematic Reviews, Web of Science Core Collection, Scopus and CINAHL databases were searched through May 2020. Articles in English evaluating the effectiveness of VI were included, without applying any date limits. Two reviewers selected articles and extracted data. RESULTS: Of the 934 articles screened, 22 articles underwent full-text article analysis to include 15 studies. There were 4 studies that reported the use of VI as a screening tool. 11 studies completely replaced FTFI with VI. Most applicants could appropriately convey themselves through VI. Most applicants and interviewing programs expressed reservations about VI’s use as an alternative to FTFI. CONCLUSION: There is dearth of evidence supporting the efficacy of VI. There is an opportunity for potential research at multi-institutional level to gain better understanding of the efficacy of VI. The knowledge obtained from this systematic review has the potential of helping applicants and institutions in preparing for VI process. Additionally, authors propose supportive strategies to help prepare applicants and institutions for VI.